The Existence of Pure and Sacred Silver Craft Creation in Gianyar Bali - I Wayan Suardana; I Made Sumantra (Institut Seni Indonesia Denpasar, 2023)
This study aims to discover in depth the existence of the creation of pure and sacred silver crafts today and the public's attention to these works. The results of this study will also be very useful for craftsmen, entrepreneurs, academics, and the government as information material about the growth and development of the creation of silverworks in an uncertain tourism situation. The decline in Bali tourism has impacted the decline in silver handicraft production in Gianyar, especially in products for tourism needs. Several areas that used to be centers of silver crafts, such as Celuk Village, Singapadu Village, and Taro Village, are now no longer productive because they rarely receive orders. In a quiet situation, some creative and highly skilled craftsmen began to divert their production by creating several pure art and sacred art as collectibles and Sesuhunan (sacred crafts) such as Barong, Rangda, and Masks which are purified and sacred by the Balinese people. The orientation of creating silverworks eventually leads to works of high quality and aesthetic value. A very interesting phenomenon to study holistically is the following: how is the existence of the creation of pure and sacred silverworks in Gianyar today? The method used in this study is a descriptive qualitative method with data collection techniques of observation, interviews, and documentation. This paper is also very appropriate to be carried out to examine in depth the development of silverworks of pure art and sacred art. There is a huge struggle between cultural and economic capital in the quest for power and the preservation of silverwork as noble works of art. This research is expected to contribute to science, especially related to arts and crafts in general.